Photoluminescence via gap plasmons between single silver nanowires and a thin gold film - Hu, Hailong (2016)
In this work, we investigate the one-photon photoluminescence from a system consisting of an Ag nanowire on an Au film with a ∼6 nm dielectric spacer that supports a localized resonance known as the gap plasmon mode. Although the Ag nanowire and Au film exhibit weak photoluminescence on their own, the combined system produces an enhanced PL emission. Our analysis reveals that the strong PL emission in this system was due to the enhanced laser absorption in, and PL emission from Au, with the Ag nanowire acting as an efficient antenna. The PL due to the gap mode is sensitive to the polarization of the laser excitation with respect to the nanowire orientation, and shows a clear dipolar emission profile. PL emission wavelengths were found to depend only on the nanowire width, and independent of its length. These observations were supported by simulation results indicating that gap plasmons are excited by light polarized transverse to the nanowire length.